Obsessive Compulsive Disorder and its Homoeopathic Management (Homoeopathy for All, 2024)
Obsessive Compulsive Disorder is  an anxiety disorder that affects 0.5  to 4% of the population in childhood  and adolescence. It is characterized  by persistent, unwanted obsessions  and compulsions. Since the exact  cause of OCD is still unknown, a  few factors, including behavioral,  cognitive, biochemical, genetic,  and environmental ones, have been  identified. The purpose of this article  is to discuss how treating OCD with  homeopathy can help an individual  improve their way of life.
Keywords: Obsessive Compulsive Disorder; Homoeopathic Manage ment.